Effect of Crab Shell Powder on Soil pH and Al-dd on Ultsiol - Muhammad Rais; Alida Lubis (Jurnal Agroekoteknologi, 2017)
This research was conducted at the Laboratory of Chemistry and Soil Fertility Faculty of Agriculture, University of North Sumatra, Medan in March 2016 to May 2016. This research aims to establish the incubation period and determine the best dosage application crab’s shell powder to increase the soil pH and aluminum adsorption in increasing available soil P on Ultisol. This research used non factorial randomized block design with three replications. Factor dosage ofcrab’s shell powder with eight treatments (0; 0.58; 1.08; 1.62; 2.16; 2.70; 3.24 and 3.78 tonnes/ha). The results of this researchhas shown that the incubation periods was significantly different inexchanging soil pH and AlddUltisol with application crab’s shell powder at 2 weeks of incubation. The best dosage of crab shell powder on soil pH, Aldd and soil available P (3.24 tonnes/ha). Application crab shell powder add C - organic soil although not significantly different at Ultisol.